2016
DOI: 10.1007/s10103-016-2017-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of incidences of bladder neck contracture of 80- versus 180-W GreenLight laser photoselective vaporization of benign prostatic hyperplasia

Abstract: Bladder neck contracture (BNC) after GreenLight laser photoselective vaporization (PVP) of benign prostatic hyperplasia is a common complication. In the present study, data of patients received 80 or 180 W PVP were collected. Perioperative parameters, including applied energy, irradiation time, catheter removal time, and hospital stay, were recorded. Postoperative parameters, including maximum urinary flow rate, International Prostate Symptom Score, post-void residual volume, and incidences of BNC, were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Histological staining in this study showed a decrease in the expression of selected inflammatory factors after vaporization compared to before treatment. As laser energy attenuates with distance from the center of the laser beam, laser therapy can produce a biological activity effect called photobiomodulation (PBM) in surrounding tissues ( 9 ). The anti-inflammatory effect is considered one of PBM’s most important biological effects ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological staining in this study showed a decrease in the expression of selected inflammatory factors after vaporization compared to before treatment. As laser energy attenuates with distance from the center of the laser beam, laser therapy can produce a biological activity effect called photobiomodulation (PBM) in surrounding tissues ( 9 ). The anti-inflammatory effect is considered one of PBM’s most important biological effects ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of laser systems for PV dates back to their initial introduction in 1998, beginning with the GreenLight KTP laser (80 W) ( 8 ), progressing to the GreenLight HPS laser (120 W), and culminating in the latest iteration known as the GreenLight XPS lasers (180 W). The GreenLight laser generator emits a pulsed laser beam characterized by a wavelength of 532 nm, a pulse width ranging from 100 to 120 ns, a frequency of 13 kHz, and a laser beam area that varies between 0.2 and 0.5 mm 2 , with a specific size contingent upon the distance between the fiber tip and the tissue surface ( 9 ).…”
Section: Introductionmentioning
confidence: 99%